Children’s e-book technology: Devices, books, and book builder - Shiratuddin, Norshuhada; Landoni, Monica (Association for the Advancement of Computing in Education (AACE), 2003)
This article describes a study of children's electronic books (e-books) technology. In particular, the focus is on devices used to access children's e-books, current available e-books and an e-book builder specifically for children. Three small case studies were conducted: two to evaluate how children accept the devices and one to test the ease of use of an existing book builder currently on the market. In addition, with the intention of finding functions that can be enhanced we also personally reviewed the book builder. A hypothesis was formed to verify the ease of use of the program. An ease of use index was constructed from the addition of four variables: (a) learning time, (b) number of questions asked during learning, (c) book building time, and (d) number of questions asked during book building. This article then concludes that children are very much at ease with e-book technology. They are able to use devices, e-books, and e-book builder without much effort.